Inovasi Desain Rak Sepatu dengan Pendekatan Weighted Matrix & Prototyping - Ezra Peranginangin; Grifine Octaviane (Jurnal Syntax Transformation, 2022)
A shoe rack is one of the household products as a place to put shoes or sandals to make it looks neat and not scattered. But there are still a lot of people who do not put it back with many reasons. One of the most selected reason based on the survey that conducted by the writer is because of the laziness to bow down and lift their shoes back to the rack. For this reason, this research aims to design of a shoe rack was carried out using several methods. The methods that used in this research are observation, survey, image board, weighted matrix, and prototyping. Started from observation on several houses that have shoe racks and observing their use, then shared an online survey to several respondents regarding the use of shoe racks, and then created shoe rack’s design concepts by making an image board, chose the final design from several alternative designs by using weighted matrix method, and finally created a product dummy with a scale of 1:5. Weighted matrix method was chosen because it can determine the alternative designs by prioritizing important aspects of the designed product, so that it will give a good result of a shoe rack for the users